Role of astrocytes in the neurogenic niches - Schneider, Julia; Karpf, Julian; Beckervordersandforth, Ruth (Astrocytes, 2019)
In the mammalian brain, highly specialized astrocytes serve as neural stem cells (NSCs) that divide and give rise to new neurons, in a process called neurogenesis. During embryonic development NSCs generate almost all neurons of the brain. Soon after birth the neurogenic potential of NSCs is highly reduced, and neurogenesis occurs only in two specialized brain regions called the neurogenic niches. Niche cells are essential to stem cells as they provide structural and nutritional support, and control fundamental stem cell decisions. Astrocytes, major components of the adult neurogenic niches, are evolving as important regulators of neurogenesis, by controlling NSC proliferation, fate choice, and differentiation of the progeny. Therefore, astrocytes contribute to neurogenesis in two ways: As NSCs and as niche cells. This review highlights the role of astrocyte-like NSCs during development and adulthood, and summarizes how niche astrocytes control the process of adult neurogenesis.
CRIS-Team Scopus Importer:2019-07-30
Keywords: Adult neurogenesis; Astrocytes; Neural stem cell niche; Neural stem cells